2013
DOI: 10.1002/hep.26219
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular endothelial growth factor in the pathophysiology of nonalcoholic steatohepatitis in two rodent models

Abstract: The pathophysiology of nonalcoholic steatohepatitis (NASH) should be approached as a multifactorial process. In several stages of NASH, a link between disease progression and hepatic microvasculature changes can be made. In this study we investigated the role of angiogenesis in two mouse models for NASH, and the effect of a preventive and therapeutic antiangiogenic treatment in a diet-induced mouse model for NASH. Protein and RNA levels of angiogenic and inflammatory factors were significantly up-regulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 55 publications
1
93
1
1
Order By: Relevance
“…Over the tested time course, several proinflammatory cytokines increased, including IL-8, IL-6, and CXCL10, all of which have established chemoattractant properties and are upregulated in NAFL/NASH patients or mouse models ( Figure 5D) (26,27). Studies have found that angiogenic factors, such as VEGF, are increased and contribute to the progression of NASH in animal models (28). In agreement, we found levels of VEGF to be increased at day 5.…”
Section: Resultssupporting
confidence: 85%
“…Over the tested time course, several proinflammatory cytokines increased, including IL-8, IL-6, and CXCL10, all of which have established chemoattractant properties and are upregulated in NAFL/NASH patients or mouse models ( Figure 5D) (26,27). Studies have found that angiogenic factors, such as VEGF, are increased and contribute to the progression of NASH in animal models (28). In agreement, we found levels of VEGF to be increased at day 5.…”
Section: Resultssupporting
confidence: 85%
“…For instance, CCL2-dependent infiltrating macrophages derived from BM into the injured liver facilitate angiogenesis during the evolution of liver fibrosis through releasing pro-angiogenic factors including VEGF [43]. Additionally, inflammatory hepatic macrophages are involved in angiogenesis with enhancement of VEGF in the progression of nonalcoholic steatohepatitis [44]. Thus, recruited macrophages are likely main mediators of sinusoidal reconstitution and hepatic angiogenesis both in acute and chronic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that neovascularization is a key element in the progression of NAFLD [56,57]. Formation of new blood vessels in chronic liver disease is linked to the advancement of fibrosis, indicating a close interplay between LSECs and HSCs.…”
Section: Hepatic Neovascularization and Altered Splanchnic Hemodynamicsmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is the master regulator of this process, mediating both pro-fibrogenic and pro-angiogenic signals and supported by HIF activation in hypoxic areas [57]. Importantly, serum VEGF levels of patients with steatosis and steatohepatitis are higher compared to healthy controls [56]. Moreover, in animal models of genetic (db/db) and methionine-choline-deficient diet (MCDD)-induced NAFLD, increased VEGF levels occur as early as 3 days into steatosis before steatohepatitis of fibrosis develops [56].…”
Section: Hepatic Neovascularization and Altered Splanchnic Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation